Punishment in the Upbringing of Children: A Bipartisan Discussion of Rev. Augustyn Jaskulski (1841–1906) and Rev. Karol Banszel (1890–1941) - Grudziński, Andrzej (Paedagogia Christiana, 2026)
The purpose of the article is to compare the pedagogical views of Rev. Augustyn Jaskulski and Rev. Karol Banszel on punishment in the upbringing of children. The considerations explain the concepts of ‘punishment’ as a method of upbringing and provide a sketch of the clergymen’s biographies. In addition, their understanding of upbringing is outlined, and views on the purposes, types and circumstances of the use of educational punishment are shown. The article concludes by outlining the similarities and differences in how the essence of punishment was understood in relation to the clergymen in question, highlighting the existence of diverse perspectives on educational punishment within the pedagogy of religion during the late 19th century, early 20th century, and the interwar period. The text is based on the analysis of the publications of the authors presented.